Extracorporeal Septoplasty: External and Endonasal Techniques - Wu, Peter S.; Hamilton, Grant S., III (Facial Plastic Surgery, 2016)
Severe septal deformities are among the most challenging problems faced by rhinoplasty surgeons. Extracorporeal septoplasty (ES)—also known as subtotal septal reconstruction—involves removal of the native deformed septum and replacement with a reconstructed neoseptum. Several techniques and multiple variations have been described in the literature. We present an overview of ES, pertinent anatomical structures and deformities, and the external versus endonasal approach, and describe some of our techniques.
Keywords: extracorporeal septoplasty; subtotal septal reconstruction; septal reconstruction; rhinoplasty; septorhinoplasty; secondary septoplasty